Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat kemiskinan dan Indeks Kemiskinan terhadap besaran APBD di Provinsi Sumatera Selatan - Lamazi Sauki; Yudi Sudihartono (Universitas Indo Global Mandiri, 2023)
Some regencies/cities that have big Regional Government Budgets (RGB) come from Revenue Sharing Fund of Natural Resource show their economicindicators are lower than other regions. This study does to knowand analyse a correlation of RGB to economic growth, poverty level and Human Development Index at 17 regencies/cities of South Sumatra Province. The research data are from 2013 to 2017 come from BPKAD and BPS, and using quantitative research method that used descriptive statisticalanalyses to test each variable and analytic statistical analyses which is used scoring analyses and simple regression analyses.Revenue Sharing Fund is a component of central government transfer as one of RGB components so the bigger Revenue Sharing Fund of a region the bigger RGB of that region. Scoring analyses shows some regions that have big RGB in 2017 do not have better rankings and vice versa, some regions that have small RGB get better rankings. Simple regression analyses, from 2013 to 2017, shows that a RGB does not have a correlation to economic growth, poverty level and Human Development Index at 17 regencies/cities of South Sumatra Province. Hence, the bigger RGB is not significant its correlation to the increasing of economic growth, the decreasing of poverty level and the increasing of Human Development Index. Keywords: Economic Growth, Poverty Level, HDI